2021
DOI: 10.1016/j.jare.2020.07.012
|View full text |Cite
|
Sign up to set email alerts
|

A novel experimental approach to evaluate guided bone regeneration (GBR) in the rat femur using a 3D-printed CAD/CAM zirconia space-maintaining barrier

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Currently, subtractive manufacturing methods are considered the gold standard for fabricating zirconia dental restorations, but AM technologies are in continuous development. Limited dental literature has assessed the potential of AM zirconia for prosthodontic dental applications 6–17 . Among the different AM technologies available to process zirconia material, vat‐polymerized AM zirconia including stereolithography (SLA), digital light processing (DLP), and lithography‐based ceramic manufacturing (LCM) methods are frequently selected in the dental field 6–11,13,15–17 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, subtractive manufacturing methods are considered the gold standard for fabricating zirconia dental restorations, but AM technologies are in continuous development. Limited dental literature has assessed the potential of AM zirconia for prosthodontic dental applications 6–17 . Among the different AM technologies available to process zirconia material, vat‐polymerized AM zirconia including stereolithography (SLA), digital light processing (DLP), and lithography‐based ceramic manufacturing (LCM) methods are frequently selected in the dental field 6–11,13,15–17 …”
mentioning
confidence: 99%
“…Limited dental literature has assessed the potential of AM zirconia for prosthodontic dental applications. [6][7][8][9][10][11][12][13][14][15][16][17] Among the different AM technologies available to process zirconia material, vatpolymerized AM zirconia including stereolithography (SLA), digital light processing (DLP), and lithography-based ceramic…”
mentioning
confidence: 99%
“…Even though the authors mimicked the bone implantation of the zirconia scaffolds via tribological tests, it is essential to verify the cell activity of the scaffolds in the biological environment. To all the above, most recently, Tetre et al, revealed a unique method for evaluating bone reconstruction using zirconia scaffolds in the rat femur via a 3D-CAD/CAM approach [70]. A thorough illustration of the design and milling of 3D-tailored CAD/CAM zirconia space-maintaining strategies for a rat femur is presented in Figure 5b.…”
Section: Computer-aided Design/computer-aided Milling (Cad/cam) Techniquementioning
confidence: 99%
“…The resorbable collagen membrane is considered the standard reference for GBR because of its good biocompatibility and biodegradability . However, the insufficient mechanical properties and fast degradation induced by proteases limit their clinical application, especially for vertical augmentation . In addition, almost all membrane products only act as a passive barrier, lacking bioactive functions, such as osteogenesis and anti-infection.…”
Section: Introductionmentioning
confidence: 99%
“…7 However, the insufficient mechanical proper-ties and fast degradation induced by proteases limit their clinical application, especially for vertical augmentation. 8 In addition, almost all membrane products only act as a passive barrier, lacking bioactive functions, such as osteogenesis and anti-infection. In this perspective, the need to engineer active barrier membranes which can favor osteogenesis in the underlying defect during GBR, protect the wound from the penetration of bacteria, and exhibit favorable mechanical behaviors is still ongoing.…”
Section: Introductionmentioning
confidence: 99%